2016
DOI: 10.21273/horttech.26.3.338
|View full text |Cite
|
Sign up to set email alerts
|

Late-season High Tunnel Planting of Specialty Cut Flowers in the Midwestern United States Influences Yield and Stem Quality

Abstract: Production and market value of U.S. grown specialty cut flowers has increased over the past several years due to stem quality issues related to long-distance transport, regional proximity to market centers, and consumer’s willingness to purchase locally. Cut flowers are traditionally grown in field or greenhouse environments; however, high tunnels provide an alternative production environment and a number of cultural and economic advantages. Specialty cut flower species ‘Campana Deep Blue’ bellflower (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Ornamental plants grown as floristic material are most often produced in specialized greenhouses, whose construction and maintenance costs are quite high. A much cheaper alternative is the cultivation of plants in an unheated foil tunnel or in field conditions [36]. Compared to field-grown crops, plants cultivated in a tunnel are characterized by higher yield, quality, and marketability [37].…”
Section: Discussionmentioning
confidence: 99%
“…Ornamental plants grown as floristic material are most often produced in specialized greenhouses, whose construction and maintenance costs are quite high. A much cheaper alternative is the cultivation of plants in an unheated foil tunnel or in field conditions [36]. Compared to field-grown crops, plants cultivated in a tunnel are characterized by higher yield, quality, and marketability [37].…”
Section: Discussionmentioning
confidence: 99%
“…Specialty and/or locally grown cut flowers may be profitable for their unique qualities, faster harvest to consumer transition resulting in a longer post-harvest vase life, and for delicate flowers which are difficult to transport without damaging (Ortiz et al, 2012;Owen et al, 2016;Wien, 2009;Yue and Hall, 2010). The increasing interest among U.S. consumers to purchase American-grown and/or locally grown flowers alongside other agricultural products (Connor, 2018;Feldmann and Hamm, 2015;Low and Vogel, 2011;Yue et al, 2011) is a value-driven trend.…”
mentioning
confidence: 99%
“…A high tunnel vs. field comparison of six cut flower species in New York, ornamental kale not included, suggested that similar transplant dates yield earlier and more concentrated harvest periods under high tunnels but did not always increase the number of stems per plant (Wien, 2009). Owen et al (2016) conducted a high tunnel and field system comparison of seven conventionally grown cut flowers from July through October in Indiana. Although ornamental kale was not included, selected cut flower species demonstrated increases in the total number of stems per week when grown under high tunnels, and stem length was greater for most flower types compared with the field (Owen et al, 2016).…”
mentioning
confidence: 99%
See 2 more Smart Citations